2017
DOI: 10.1007/s00259-017-3681-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of repeated cycles of radioligand therapy using [177Lu]Lu-PSMA-617 on renal function in patients with hormone refractory metastatic prostate cancer

Abstract: Renal toxicity in patients treated with [Lu]Lu-PSMA-617 was low. There was no (sub)acute grade 3 or 4 nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 19 publications
5
79
0
3
Order By: Relevance
“…The radiolabeling, administration, and treatment procedures in this study were conducted using previously described methods . The median administered activity per cycle was 6.2 GBq (total range of 3.2‐7.5 GBq).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiolabeling, administration, and treatment procedures in this study were conducted using previously described methods . The median administered activity per cycle was 6.2 GBq (total range of 3.2‐7.5 GBq).…”
Section: Methodsmentioning
confidence: 99%
“…However, PSMA‐RLT is still considered a last‐line treatment option, as data from prospective randomized phase III trials are lacking . According to recent studies, PSMA‐RLT seems to be safe and effective, even for patients with advanced PC or multiple PC relapses following several therapies . In the literature, the typical length of time that patients live posttreatment ranges between 7.5 and 15 months …”
Section: Introductionmentioning
confidence: 99%
“…The kidneys are a possible dose‐limiting organ because of the predominant renal excretion of PSMA ligands . The high uptake of 177 Lu‐ and 225 Ac‐labelled PSMA ligands in kidneys is usually observed short time (1‐4 hours) after injection of the radioligands, in both mice and humans .…”
Section: Introductionmentioning
confidence: 99%
“…25 The kidneys are a possible dose-limiting organ because of the predominant renal excretion of PSMA ligands. 26 The high uptake of 177 Lu-and 225 Ac-labelled PSMA ligands in kidneys is usually observed short time (1-4 hours) after injection of the radioligands, in both mice and humans. 27,28 With shorter-lived radionuclides like 212 Pb (t 1/2 ≈10.6 hours) and 211 At (t 1/2 ≈7.2 hours), the initial kidney uptake could represent a potential toxicity problem since a high dose will be delivered to the kidneys within the first few hours.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown no evidence of grade 3/4 toxicity in patients with neuroendocrine tumors after repeated (≥8 cycles) radiopeptide therapy with a cumulative dose of up to 97 GBq 12. Good tolerability has also been observed in patients with prostate cancer (PC) after a cumulative dose of 36 GBq and up to six cycles of radioligand therapy 13,14…”
Section: Introduction: Goals Of Theranostics In Nuclear Medicinementioning
confidence: 99%